The need for future research into the assessment and monitoring of eating disorder risk in the context of obesity treatment. Issue 5 (24th January 2023) - McMaster, Caitlin M.; Paxton, Susan J.; Maguire, Sarah; Hill, Andrew J.; Braet, Caroline; Seidler, Anna L.; Nicholls, Dasha; Garnett, Sarah P.; Ahern, Amy L.; Wilfley, Denise E.; Lister, Natalie B.; Jebeile, Hiba
Abstract: In adolescents and adults, the co‐occurrence of eating disorders and overweight or obesity is continuing to increase, and the prevalence of eating disorders is higher in people with higher weight compared to those with lower weight. People with an eating disorder with higher weight are more likely to present for weight loss than for eating disorder treatment. However, there are no clinical practice guidelines on how to screen, assess, and monitor eating disorder risk in the context of obesity treatment. In this article, we first summarize current challenges and knowledge gaps related to the identification and assessment of eating disorder risk and symptoms in people with higher weight seeking obesity treatment. Specifically, we discuss considerations relating to the validation of current self‐report measures, dietary restraint, body dissatisfaction, binge eating, and how change in eating disorder risk can be measured in this setting. Second, we propose avenues for further research to guide the development and implementation of clinical and research protocols for the identification and assessment of eating disorders in people with higher weight in the context of obesity treatment. Public Significance: The number of people with both eating disorders and higher weight is increasing. Currently, there is little guidance for clinicians and researchers about how to identify and monitor risk of eating disorders in people with higher weight. We present limitations of current research and suggest future avenues for research to enhance care for people living with higher weight with eating disorders.